Analisis Kas Kecil Dalam Sistem Akuntansi Kas Pada PT Paya Pinang - Wifka Yunita; Kusmilawaty Kusmilawaty (Jurnal Riset Akuntansi, 2024)
The formation and use of cash is a delegation of authority to petty cash holders to pay directly for relatively small cash expenditures. This research aims to analyze procedures for the formation, accountability and filling of petty cash at PT. PD. Paya Pinang. This research uses qualitative methods with primary data sources. Data collection by interviews and documentation in the form of recording procedural data contained in the procedure book which is kept in the finance section. The results of this research show that petty cash in the cash accounting system at PT. PD Paya Pinang's formation, accountability and replenishment procedures have been carried out efficiently and effectively using a fixed fund system (Imprest find) because it has gone through the procedures established by the company.